Present Methods of Data Assimilation in the U.S. Navy's Sea Ice Forecasting Models - Preller, Ruth H.; Posey, Pamela G. (1989)
The U.S. Navy presently has two sea ice forecasting systems running on a daily operational schedule at the Fleet Numerical Oceanography Center. The first forecast system, the Polar Ice Prediction System (PIPS), covers the Arctic basin, The Barents Sea and the Greenland Sea using 125 km grid resolution. The second model, the Regional Polar Ice Prediction System-Barents (RPIPS-B), cover the Barents Sea and western have of the Kara Sea using 23 km grid resolution. Both models are forced by atmospheric forcing from the Naval Operational Global Atmospheric Prediction System and monthly mean geostrophic ocean currents and deep ocean heat fluxes. The models are run daily making 120 hour forecasts of drift, ice thickness and ice concentration. Both models are updated, once per week, by assimilating digitized concentration data from the Naval Polar Oceanography Center. Accuracy in the digitized data as well as the timeliness of the data shown to have a serious impact on the model forecasts.